HUBUNGAN PEMAHAMAN GURU DENGAN PENERAPAN PENDIDIKAN SEKS BAGI ANAK USIA 4-6 TAHUN - Elina, Ernamitha; Ali, Muhamad; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the relationship between teacher comprehension and the application of sex education for children aged 4-6 years at Southeast Pontianak District. The method used is the quantitative method of correlation, the research subjects are 10 teachers who teach in group A and group B. The Questionnaires are used in collecting data for this research. The results showed that the application of sex education to children aged 4-6 years in this study was very good, with an average of 85% of teachers giving sex education to children aged 4-6 years. There is a positive and significant relationship between teacher comprehension and the application of sex education in children aged 4 to 6 years which has a very strong relationship. The results show that when comparing r-count with r-table, where N=10, at a significance level of 5%, we get r-count 0.983 r-table 0.632 r count 0.983. Thus it can be concluded that there is a significant and positive relationship between teacher comprehension and the application of sex education for children aged 4-6 years at Southeast Pontianak District.